Optimization of extraction conditions on physicochemical properties of identified compounds from Solanum lycopersicum and Daucus carota L. for lip balm formulation - Nur Solehin Sulaiman (2023)
Tomato and carrot are plants rich in lycopene and B-carotene, where both plants provide many health benefits, mainly to human skin, especially lips. The most common lip problem is chapping due to frequent lip licking, sun-related damage, and dehydration. Lip balm acts as a moisturizer and can be formulated from plant origins such as tomatoes and carrots. However, there is still a lack of studies that have been conducted on the formulation of lip balm using a combination of tomatoes and carrots to overcome lip problems. Thus, this study aimed to optimize the extraction conditions on the physicochemical properties of identified compounds from Solanum lycopersicum and Daucus carota L. for lip balm formulation. This study comprised two main parts of methodology, which were extraction and formulation parts. In the first part, two drying methods (dehydrator and oven) were applied to both plant samples before extracting them using the maceration technique under Ultrasonic Assisted Extraction (UAE) conditions. Design Expert Software-12 was used to find the optimum extraction yield under three parameters. The optimum extraction yields were then tested for antioxidant, Total Flavonoid Compound (TFC), and Total Phenolic Compound (TPC) using the Thin Layer Chromatography (TLC) technique. Besides, the morphological image (before and after extraction) was examined using scanning electron microscopic. Gas Chromatography-Mass Spectrometry (GC-MS) was applied to detect any pesticides in the sample of optimum yields. The second part began with the utilization of Design Expert Software-12 in formulating lip balm, where the optimum formulation was selected based on the five physicochemical analyses. The Design Expert Software-12 set nineteen formulations with three factors. The optimum formulations were tested for the stability test in two conditions (room temperature and chiller) for a month and microbial growth test in 24 hours. Besides, this optimum formulation was compared with the commercial product. The result for the first part of the method presented the optimum parameters for both drying methods at a temperature of 53 °C, 60% of ethanol concentration and 3.5 hours of extraction time with the yield of 1.33 g, 1.41 g, 1.28 g and 1.31 g for tomato (oven drying), tomato (dehydrator drying), carrot (oven drying) and carrot (dehydrator drying) respectively. Rf value of antioxidant, TPC and TFC for all four optimum extraction yields were equal to a value of 0.95. Morphological images showed that after the extraction process, the porosity and loosened damaged cell structure indicated that all bioactive compounds in the plant cell were extracted. It was found that no pesticides were detected in the optimal extraction yield samples. As for the second part of the method, the optimal formulation (2.38 g, 2.38 g, 0.15 g and 0.05 g for the beeswax, cocoa butter, tomato extract and carrot extract, respectively) showed stability in both conditions without microbial growth in the agar plate. In addition, the optimal formulation presented physicochemical properties comparable to the commercial lip balm. This study proved that the tomatoes and carrots extracts could be incorporated in lip balm formulation and show equivalent physicochemical properties to commercial products. Therefore, the formulated lip balm could be commercialized after several dermal tests.